2003
DOI: 10.1007/s00296-003-0369-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of atopy in rheumatoid arthritis in Sivas, Turkey. A prospective clinical study

Abstract: Assumed mutual antagonism of T-helper cell (Th)1 and Th2 diseases suggests that the prevalence of atopy should be decreased in rheumatoid arthritis (RA). We tried to determine that prevalence. Sixty-two patients with RA and 61 with osteoarthritis (control group) were included in the study. A questionnaire was used concerning mainly the symptoms of atopy. Skin prick tests, pulmonary function tests, chest X-rays, immunoglobulin E levels, and eosinophil counts were obtained. The prevalences of asthma, hay fever, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 19 publications
2
17
0
5
Order By: Relevance
“…In a previous series, 1% patients had an atopic skin disease,[6] which is comparable to another study conducted by Kaptanoglu et al ., in which 1.6% of RA patients had atopic dermatitis. [24] However, there was no patient with atopic dermatitis in the present series. Overall, atopic skin diseases seem to be less common in RA patients than in the general population.…”
Section: Discussionmentioning
confidence: 56%
“…In a previous series, 1% patients had an atopic skin disease,[6] which is comparable to another study conducted by Kaptanoglu et al ., in which 1.6% of RA patients had atopic dermatitis. [24] However, there was no patient with atopic dermatitis in the present series. Overall, atopic skin diseases seem to be less common in RA patients than in the general population.…”
Section: Discussionmentioning
confidence: 56%
“…Nonetheless, the main conceptual limitation of the current literature is a failure to recognize asthma “as a chronic inflammatory disease with systemic inflammatory features that go beyond the airway.” Emerging evidence suggests that asthma poses a significant impact on immune dysfunction and dysregulation at a systemic level in both adults and children in a way that poses them at risk for significantly higher morbidity and mortality from ARC23242526272829323334353637383940414247484950515253545657585960616263136137. In this regard, the current literature suggests that asthma poses a significantly increased risk of RA in subjects with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…There are five studies available in the literature which showed no association between asthma and the risk of RA (Table 4): one population-based retrospective cohort study33, three case-control studies606162, and one cross-sectional study63.…”
Section: Asthma and Risk Of Ramentioning
confidence: 99%
See 2 more Smart Citations